STUDY OF PARAMETERS OF FELLING HEAD ELEMENTS OF A ONE-GRIP FELLER BUNCHER FOR CLEARING AGRICULTURAL LANDS AND AGROFORESTRY - Lastochkin, Denis Mihailovich; Onuchin, Evgeny Mihailovich; Medyakov, Andrey Andreevich; Kostromin, Denis Vladimirovich; Ostashenkov, Aleksey Petrovich (Journal of Applied Engineering Science, 2017)
The purpose of this article is the theoretical justification of parameters of the felling head elements and experimental studies of the work technique of a one-grip front feller buncher on the basis of the tractor of the drawbar category 0.6-1.4 (16-55 kW). The essence of theoretical study is to determine parameters of the mounted felling head for cutting and vertical holding of a tree of a diameter of 10 to 22 cm, taking into account the optimal working zone of the tilt mechanism. Experimental study was carried out on a prototype of a one-grip feller buncher of the front type (based on the T-25 tractor) with the mounted felling head. In the process of carrying out field studies, technological performance parameters of a one-grip feller buncher for low-capacity logging and the pressure in the hydraulic system of the felling head were studied under various operating conditions.
Keywords: Felling head; Tilt mechanism; Recultivation of old agricultural lands